2013
DOI: 10.1590/s1414-462x2013000300012
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da completitude dos instrumentos de investigação do óbito infantil no município de Arapiraca, Alagoas

Abstract: OBJETIVO: Avaliar a completitude dos instrumentos de investigação do óbito infantil no nível municipal. MÉTODOS: Estudo avaliativo, descritivo da completitude e grau de preenchimento das fichas de investigação de óbitos não fetais de menores de um ano residentes em Arapiraca, Alagoas (outubro de 2009 a dezembro de 2010). Para cada variável calculou-se percentual de completitude (Epi-Info v. 3.4.2) e grau de preenchimento. RESULTADOS: Dos 81 óbitos existentes, 54,32% foram investigados através da ficha domicili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
1
13

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(33 citation statements)
references
References 22 publications
0
19
1
13
Order By: Relevance
“…The Hospital Form had a higher frequency of filling-in, different from the reality found in another municipality of the Northeast with child deaths in 2009 and 2010 15 . This can be explained by the fact that the majority of stillbirths of residents in Jaboatão in 2014 were born in Recife and in establishments that had Hospital Epidemiology Group which, given the mandatory character form contributed to collection of important information from the Outpatient and Hospital Forms, since their blocks deal with data on the care given in those establishments.…”
Section: Discussioncontrasting
confidence: 71%
See 3 more Smart Citations
“…The Hospital Form had a higher frequency of filling-in, different from the reality found in another municipality of the Northeast with child deaths in 2009 and 2010 15 . This can be explained by the fact that the majority of stillbirths of residents in Jaboatão in 2014 were born in Recife and in establishments that had Hospital Epidemiology Group which, given the mandatory character form contributed to collection of important information from the Outpatient and Hospital Forms, since their blocks deal with data on the care given in those establishments.…”
Section: Discussioncontrasting
confidence: 71%
“…The information on the outpatient data had a lower number of forms filled in (1:8) and also the worst degree of filling-in (61.5%) of the forms analyzed. Caetano, Vanderlei and Frias (2013) also found lower completeness in the Outpatient Form for infant deaths in Arapiraca, in the State of Alagoas 15 . Surveys on quality of medical records in Basic Healthcare Units indicated that information of implications in continuity of care were precarious 19 .…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…10 In the surveillance assessments conducted in Brazil, the strategy is considered a management tool capable of providing information to health teams, generating critical awareness on the offered care, and enhancing information systems. 11,16,17 Moreover, it can be used to plan interventions for the main problems and barriers of the care system and to reduce preventable deaths and iniquities. 6 Given its potential, mortality surveillance generates special interest for the monitoring actions required to achieve the Sustainable Development Goals.…”
Section: Introductionmentioning
confidence: 99%